The Political Conflicts and the Division of the Carolingian Empire214-229AH\829-843AD. (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The Carolingian Empire which was established by Emperor Charlemagne in (184AH / 800AD) remained strong throughout his life until his death in (199AH / 814 AD), but his son Louis the Pious (199-226 AH / 814-840 AD) who succeeded him to the throne was unable to preserve the Empire. So, he divided it between his sons following the steps of the Franks. This division led to the outbreak of the civil wars Inside the Carolingian Family. The situation aggravated terribly after his death which led to the division of the Empire between his three sons under theTreaty of Verdun, but wars and political conflicts have continued between the three Kingdoms. These conflicts in the Carolingian Empire will be the subject of the study.